2002
DOI: 10.1002/ppul.10039
|View full text |Cite
|
Sign up to set email alerts
|

Congenital bronchoesophageal fistula and tracheoesophageal fistula with esophageal atresia

Abstract: A case of initial esophageal atresia and tracheoesophageal fistula in a female newborn, later complicated by pneumonia and a second bronchoesophageal fistula, is reported. She was treated surgically by closure of the tracheoesophageal fistula and by end-to-end esophago-esophageal anastomosis. An esophagram at 1 month of age was normal. Three months later she developed severe, persistent right lower lobe pneumonia that required intensive antibiotic therapy and respiratory support. Esophagography was repeated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Braimbridge and Keith [3] classified congenital BEF into four types. Type II BEF is most common in adults, but rare in neonates [2]. Here, we report a neonate who presented with type II BEF, which was difficult to diagnose prior to surgery.…”
Section: Congenital Bronchoesophageal Fistula Repaired By Bronchoscopmentioning
confidence: 88%
See 2 more Smart Citations
“…Braimbridge and Keith [3] classified congenital BEF into four types. Type II BEF is most common in adults, but rare in neonates [2]. Here, we report a neonate who presented with type II BEF, which was difficult to diagnose prior to surgery.…”
Section: Congenital Bronchoesophageal Fistula Repaired By Bronchoscopmentioning
confidence: 88%
“…Thirdly, an esophageal fold or membrane flap may create a check valve to mask the fistula. In other words, MDCT cannot definitely detect the disease because of tiny lesions or the respiratory motion artifacts, especially in neonates [2].…”
Section: Congenital Bronchoesophageal Fistula Repaired By Bronchoscopmentioning
confidence: 99%
See 1 more Smart Citation
“…One study identified 105 cases of bronchopulmonary fistula, with only 20 diagnosed in children younger than 15 years [2]. Another study looked at 100 cases, with 24 in the pediatric population [3]. The reasons for delayed diagnosis are poorly understood but are likely due to vague presentation in many patients.…”
Section: Discussionmentioning
confidence: 98%
“…This is definitively diagnosed only on histological examination by the absence of surrounding inflammation, the absence of adherent lymph nodes and the presence of a mucosa and muscularis mucosa. [5,6] The most common location of BOFs is between the middle third of the oesophagus and the right lower lobe (41%), followed by the left lower lobe (21%), right main bronchus (18%), bronchus intermedius (10%), left main bronchus (6%), right middle lobe (2%) and right upper lobe (2%). [3,5] Symptoms of BOFs are insidious, occasionally beginning in childhood but rarely at birth.…”
Section: Broncho-oesophageal Fistulasmentioning
confidence: 99%